Peristalsis and regulation of gastrointestinal motility: From mechanisms to pathophysiology - Halinska, A. M.; Severynovska, O. V.; Halinskyi, O. O. (Regulatory Mechanisms in Biosystems, 2025)
Gastrointestinal motility is determined by a complex interaction of neuronal, humoral, and cellular-muscular mechanisms that ensure the movement of partially digested food along the gastrointestinal tract, regulate digestion processes, and control sphincter function. This review presents a systematic study of the anatomical and functional organization of the gastrointestinal tract with a special emphasis on peristalsis and coordination of sphincter activity. Particular attention is paid to the structural and functional role of the SIP syncytium, including interstitial cells of Cajal, cells expressing platelet-derived growth factor receptor-α, and smooth muscle cells in the generation of slow waves and intercellular signaling. Important molecules like calcium ions, nitric oxide, and inositol triphosphate, which are crucial for starting and adjusting muscle contractions, are examined. The data on neurohumoral regulation of motility involving such mediators and peptides as acetylcholine, vasoactive intestinal peptide, motilin, cholecystokinin, and glucagon-like peptide-1 are also summarized. The differences in how motility is controlled based on sex and age are examined, particularly how estrogens and nitric oxide signaling affect this. The pathophysiology of central motility disorders, including esophageal achalasia, functional dyspepsia, gastroesophageal reflux disease, and duodenogastric reflux, is studied, considering the role of esophageal hernia. Modern diagnostic methods are considered, including high-precision manometric study, functional lumen assessment technologies, and long-term monitoring of acidity in the esophagus. The pr e sented data emphasize the close relationship between the molecular mechanisms, cellular structure and clinical manifestations of gastrointestinal motility disorders. The study highlights the need for an integrative and interdisciplinary approach to analyzing gastrointestinal motility, which can improve diagnostic accuracy and enable personalized treatment.